Risk factors for leakage after total gastrectomy (Annals of Medical Research, 2021)
Aim: Although many studies report risk factors for anastomotic leakage after gastrectomy for gastric cancer (GC), there are conflicting results in the literature. In this study, we aimed to identify the risk factors associated with anastomotic leakage after gastrectomy. Material and Methods: Patients who underwent total gastrectomy for gastric cancer in a single center between September 2015 and September 2018 were evaluated retrospectively. The relationship between anastomotic leakage and clinical variables, tumor characteristics and intraoperative characteristics of 18 parameters were analyzed. The relationship between anastomotic leakage and survival was evaluated.Results: A total of 102 patients were included in the study. Anastomotic leakage rate was 9.81% (10/102). A significant relationship was not determined between anastomotic leakage and age >60 (p:0.232), diabetes mellitus (p:0.334), ASA score >3 (p:0.587), albumin 300 (p:0.582), and operation duration >300 min (p:0.176). Multivariate regression analysis, showed female sex (p: 0.05), body mass index (BMI) >30 (p:0.024) and tumor localization (p:0.005) are independent risk factors for anastomotic leakage. There was a significant difference in mean survival between patients with and without anastomotic leakage (13.9 vs 34.9 months, p: 0.006). Conclusion: Anastomotic leakage was associated with female sex, obesity, and tumor location. We also found that anastomotic leakage adversely affects long-term survival. Detecting risk factors after gastrectomy guides us in the management of patients at the risk for anastomotic leakage.
Keywords: Gastrectomy; complication; anastomotic leak